PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA POSTER TERHADAP PENGETAHUAN REMAJA PUTRI DALAM MENGHADAPI MENARCHE DI SD YOS SUDARSO II KOTA BATAM - Kelara Emelia Br Ginting; Aryaneta, Yenni; Abd Hafid, Rachmawati (Universitas Batam, 2025)
Menarche is the first menstrual event for a woman and needs special attention, because it marks the beginning of a woman's maturity. Their ignorance of reproductive health can cause various diseases such as reproductive tract infections. Health promotion is carried out by adopting poster media as a means of conveying information. Posters are image media that combine visual elements such as lines, images and words to attract attention and simple but effective designs are proven to be able to optimize the appeal of posters for general students. The purpose of this study is to determine the effect of health education using poster media on the knowledge of young women in facing menarche. The research method uses a one-group pretest-posttest design approach, on 30 young women with a sampling technique using total sampling and using a knowledge questionnaire about menarche to measure the level of knowledge of young women about menarche. The results of the study obtained the level of knowledge of adolescent girls before being given health education (20.30), and after being given health education (22.20),) P value was 0.001 < 0.05, so. so there was a significant difference in the level of knowledge of adolescent girls before and after being given health education through poster media. It can be concluded that providing health education through poster media is effective in increasing the knowledge of adolescent girls related to readiness to face menarche Keywords: Health Education, Menarche, Poster Media, Knowledge